2019
DOI: 10.1101/525162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling enamel matrix secretion in mammalian teeth

Abstract: 22 39 matrix deposition can be used to predict occlusal morphologies of teeth. 40 41

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
7
0
4
Order By: Relevance
“…6,15 The ideal approach to remineralisation is to reconstruct HA crystals, which are the inorganic component of enamel, typically via the application of fluorides. 19 Clinically applied fluorinated varnish adheres to the enamel surface and creates a CaF 2 layer, which constitutes a physical barrier against acid-related changes. 25,26 However, studies evaluating the effect of fluorides on remineralisation have revealed limitations in the ability of fluoride ions alone to explain the enamel response to acidic attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,15 The ideal approach to remineralisation is to reconstruct HA crystals, which are the inorganic component of enamel, typically via the application of fluorides. 19 Clinically applied fluorinated varnish adheres to the enamel surface and creates a CaF 2 layer, which constitutes a physical barrier against acid-related changes. 25,26 However, studies evaluating the effect of fluorides on remineralisation have revealed limitations in the ability of fluoride ions alone to explain the enamel response to acidic attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel is 87.1% inorganic substances, 11.5% water and 1.4% organic substances. 19 CPP-ACP, fluoride-containing CPP-ACP, HA,…”
mentioning
confidence: 99%
“…Despite understanding the heritability of some aspects of dental morphology, 91,92 we have no understanding of the heritability of biomechanically relevant aspects of molar occlusal morphology and how it relates to EDJ shape and/or enamel secretion patterns in primates. 93 This is necessary to construct evolutionary models to (a) understand how selection is acting on dental topography and (b) perform more accurate dietary reconstructions, by understanding how long it takes teeth to become adapted to diet. Here, the biggest challenge lies in gaining a pedigreed collection of unworn dental molds: worn teeth cannot be used for these purposes, as their shape is a product of genetic and environmental factors.…”
Section: Heritabilitymentioning
confidence: 99%
“…The unified models described above are not exhaustive, and do not account for a number of other events experimentally shown to contribute to pattern formation. Tissue growth, for instance, was modelled in studies of mouse digit and teeth patterns [ 41 , 48 , 56 , 57 ] or periodic stripes in zebra fish tailfins [ 58 , 59 ], but reciprocal interactions between molecular, cellular, and mechanical mechanisms remain absent from most models. For example, all known cellular and molecular markers of follicle differentiation, from cell proliferation to the fluctuation of molecular expression, may be generated or affected by intrinsic mechanical properties of the cutaneous tissue.…”
Section: Designing Numerical Evo-devo Approaches To Study Tissue Mmentioning
confidence: 99%